Mass spectrometry‐based cortisol profiling during adrenal venous sampling reveals misdiagnosis for subtyping primary aldosteronism. (30th December 2021) - Ma, Ying; Chen, Hong; Chen, Fangjun; Jiang, Jingjing; Guo, Wei; Li, Xiaoying; Gao, Xin; Lu, Zhiqiang; Zhou, Bo; Zhao, Lin; Li, Xiaomu
Abstract: Objective: Primary aldosteronism (PA) is a common form of secondary hypertension. Adrenal venous sampling (AVS) is the gold standard for subtyping PA. This study aimed to determine whether there is a difference between immunoassays and liquid chromatography‐mass spectrometry (LC‐MS/MS) methods for measuring cortisol levels that affect the judgement of AVS. Design: This was a retrospective study. Patients: Included 72 patients who were diagnosed with PA and had undergone AVS. Measurements: Patients were grouped according to whether they received adrenocorticotropic hormone (ACTH) stimulation during AVS, and the cortisol results were measured using immunoassay and LC‐MS/MS. Results: There were 48 patients in the without ACTH stimulation group and 24 in the post‐ACTH stimulation group during AVS (bilateral adrenal vein cannulation success rate, 56.25% vs. 83.33%). ACTH stimulation was beneficial for increasing the success rate of AVS ( p < .001). Immunoassays were linearly correlated with LC‐MS/MS when cortisol concentrations were <1750 nmol/L ( r = .959, p < .001). When cortisol concentrations were >17, 500 nmol/L, no correlation was found between the two methods ( p = .093). The two methods were consistent for the detection of cortisol for evaluating the success of cannulation for AVS. Five percent of patients showed discordant lateralization of aldosterone production according to the cortisol LC‐MS/MS and immunoassay results in the without ACTH group, and 15% showed discordant lateralization in the post‐ACTH group. Conclusions: The immunoassay method can be used to determine whether cannulation is successful. The final decision for lateralization may be more appropriate based on LC‐MS/MS results.